A New Carbon Phase Constructed by Long‐Range Ordered Carbon Clusters from Compressing C70 Solvates. (16th September 2014) - Cui, Wen; Yao, Mingguang; Liu, Shijie; Ma, Fengxian; Li, Quanjun; Liu, Ran; Liu, Bo; Zou, Bo; Cui, Tian; Liu, Bingbing
<x xml:space="preserve">Abstract</x> An ordered amorphous carbon cluster (OACC) structure with building blocks of highly deformed/collapsed C70 is synthesized by compressing C70*m‐xylene, which exhibits an exceptionally high hardness. Different from compressing C60*m‐xylene, a new structure transition is observed in C70*m‐xylene at above 30 GPa, indicating the formation of a new OACC structure under pressure <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>